Risk factors associated with musculoskeletal symptoms in Korean dental practitioners - Cho, Hwi-young; Han, Gyeong-Soon; Cho, KiHun (Journal of Physical Therapy Science, 2016)
[Purpose] The purpose of this study was to investigate the association between psychosocial stress, occupational stress, and musculoskeletal symptoms in Korean dental practitioners. [Subjects and Methods] Self-reported questionnaires were distributed to 401 dental practitioners in Korea. To assess the risk factors related to musculoskeletal disorders, the Nordic Musculoskeletal Questionnaire, the Korean Occupational Stress Scale, and Psychosocial Well-Being Index Short Form were used. General and work-related characteristics of the subjects consisted of seven items, including age, career, height, weight, working days/week, working hours/day, and physical strain levels. [Results] In this study, 86.8% of the practitioners experienced musculoskeletal symptoms (shoulders, 72.8%; neck, 69.3%; waist, 68.3%; wrist, 58.4%; back, 44.1%; ankle, 38.7%; knee, 36.9%; hip, 20.4%; and elbows, 9.2%). Moreover, psychosocial and occupational stress can affect the occurrence of musculoskeletal disorders. In particular, we found that psychosocial stress has significant influence on the occurrence of musculoskeletal disorders. [Conclusion] To increase the quality of life and provide high-quality medical service for dental practitioners, risk factors for musculoskeletal disorders must be managed. Accordingly, dental practitioners must maintain good posture, get an appropriate amount of rest, and perform regular stretching exercise to reduce psychological stress and improve the work environment.